Confirmatory factor analysis of the Pittsburgh Sleep Quality Index in women with hot flashes. Issue 11 (November 2015) - Otte, Julie L.; Rand, Kevin L.; Landis, Carol A.; Paudel, Misti L.; Newton, Katherine M.; Woods, Nancy; Carpenter, Janet S.
Abstract: Objective: Women, especially those with hot flashes, report poor sleep quality during various stages of the menopausal transition and postmenopause. Sleep measurements vary widely because of the copious instruments available. The Pittsburgh Sleep Quality Index (PSQI) is a frequently used questionnaire that produces a single score for sleep quality. This one-factor structure has not received consistent support in the literature. The goal of this analysis was to determine the best factor structure of the PSQI in women with hot flashes. Methods: A confirmatory factor analysis was conducted on PSQI baseline data from three randomized controlled clinical trials enrolling perimenopausal and postmenopausal women with hot flashes (N = 849) from the Menopause Strategies: Finding Lasting Answers for Symptoms and Health network. Several a priori factor models were compared. Results: One-factor and two-factor models did not fit the data. A three-factor model comprising sleep efficiency, perceived sleep quality, and daily disturbance showed good fit; however, the sleep medication item was dropped because of poor fit and low rates of sleep medication use. The three-factor model was examined in African-American and white subsamples and was found to be similar in both groups; however, two items showed small group differences in strength as indicators. Conclusions: Sleep quality in midlife women with hot flashes, as measured by the PSQI, seems to comprise three correlated factors. Minor measurement differences detected between groups are of research interest but do not necessitate different scoring practices. Additional research is needed to further define sleep quality and its associations with health-related outcomes.